2018
DOI: 10.1002/jcp.26414
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells in lung repair and regeneration: Current applications and future promise

Abstract: Lung diseases are major cause of morbidity and mortality worldwide. The progress in regenerative medicine and stem cell research in the lung are currently a fast-growing research topic that can provide solutions to these major health problems. Under normal conditions, the rate of cellular proliferation is relatively low in the lung in vivo, compared to other major organ systems. Lung injury leads to the activation of stem/progenitor cell populations that re-enter the cell cycle. Yet, little is known about stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…These cells may be abrogated during H7N9 infection, so that epithelial damage worsens the ongoing pneumonia, thereby leading to the death of these patients. In addition to traditional treatments, novel therapies, such as stem-cell therapy, could be developed to reduce mortality by enhancing lung regeneration in patients with ARDS [ 20 , 58 ]. Moreover, small molecules that could boost the regenerative capacity of epithelial stem/progenitor cells should be screened by the drug industry.…”
Section: Discussionmentioning
confidence: 99%
“…These cells may be abrogated during H7N9 infection, so that epithelial damage worsens the ongoing pneumonia, thereby leading to the death of these patients. In addition to traditional treatments, novel therapies, such as stem-cell therapy, could be developed to reduce mortality by enhancing lung regeneration in patients with ARDS [ 20 , 58 ]. Moreover, small molecules that could boost the regenerative capacity of epithelial stem/progenitor cells should be screened by the drug industry.…”
Section: Discussionmentioning
confidence: 99%
“…Although ALI pathophysiology and treatments have been investigated in many studies, effective pharmacotherapies or therapeutic strategies are limited [ 11 ]. MSCs may be a promising alternative for treating lung diseases [ 12 , 13 ], as increasing evidence supports the therapeutic effects of MSCs in pulmonary fibrosis, bronchopulmonary dysplasia, chronic obstructive pulmonary disease, and ALI. Recent studies have also shown that transplantation of MSCs from the bone marrow, umbilical cord (UC), menstrual blood (MB), and adipose tissue can attenuate lung injury and inflammatory responses [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, resident multipotent lung stem cells were isolated and wellcharacterized from adult mouse lung (97,98). Lung resident stem cells can produce different types of cytokines, growth factors and surfactant proteins, which are specific biomarker of the lung (35,38,39,96,(99)(100)(101).…”
Section: Endogenous Lung Tissue-specific Stem Cellsmentioning
confidence: 99%